QUANTITATIVE EVALUATION OF VITAMIN COMPOSITION IN BITTER WORMWOOD EXTRACTS AND ITS PHARMACOLOGICAL RELEVANCE - Marupova Manzura Aminovna (Modern American Journals, 2025)
This study presents a detailed chromatographic analysis of the vitamin composition in Artemisia absinthium L. (bitter wormwood), focusing on its pharmacological and biochemical significance. Using high-performance liquid chromatography (HPLC), seven key vitamins — B₁, B₂, B₃, B₆, B₉, B₁₂, and PP — were quantitatively evaluated in ethanolic and aqueous extracts obtained from wild and cultivated plant samples collected in the Fergana Valley, Uzbekistan. The results revealed that cultivated wormwood contains slightly higher total vitamin content than wild specimens, particularly in niacin (B₃), riboflavin (B₂), and nicotinamide (PP). These vitamins contribute to the plant’s strong antioxidant, detoxifying, and metabolic activities, enhancing its therapeutic potential. The study highlights the dual ecological and pharmacological importance of A. absinthium as a natural source of essential vitamins and as a model plant for sustainable medicinal resource development in arid environments.
Keywords: Artemisia absinthium L.; bitter wormwood; vitamins B₁–B₁₂; nicotinamide; HPLC; chromatographic analysis; Fergana Valley; pharmacological relevance; antioxidant activity; medicinal plants; phytochemistry; nutraceutical potential; sustainable agriculture; bioactive compounds.